2015
DOI: 10.1099/mic.0.000136
|View full text |Cite
|
Sign up to set email alerts
|

Identification serologically, chemically and genetically of two Escherichia coli strains as candidates for new O serogroups

Abstract: Escherichia coli strains are normally identified by the combination of their O and H (and sometimes K) antigens, and serotyping based on the antigens is believed to be crucial for clinical detection and epidemiological investigation. Two E. coli strains, G5413 and G5287, were isolated from faecal samples of female patients with diarrhoea and were not agglutinated with any antisera that cover the well-known O serogroups of E. coli. We elucidated the Opolysaccharide (OPS) structures and analysed the O-antigen ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Three distinct pathways participated in the synthesis and translocation of OPS: the Wzx/Wzy pathway, the ATP-binding cassette (ABC) transporter pathway (Hu et al, 2013), and the synthase pathway. O-antigen serotyping, targeting the wzx and wzy genes, is able to detect distinct O-antigen forms, including E. coli , Shigella , Salmonella , Vibrio parahaemolyticus , Acinetobacter , Hafnia , and Proteus (Li et al, 2009, 2010; Guo et al, 2013; Hu et al, 2013; Chen et al, 2015; Duan et al, 2016; Yu et al, 2017). Our previous studies employed wzx and wzy for serotyping E. coli and Shigella by microarray (Li et al, 2006), wzx and wzy for serotyping Pseudomonas aeruginosa (Li et al, 2018) and wzm and wzt for serotyping 15 Legionella pneumophila serogroups by microarray (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct pathways participated in the synthesis and translocation of OPS: the Wzx/Wzy pathway, the ATP-binding cassette (ABC) transporter pathway (Hu et al, 2013), and the synthase pathway. O-antigen serotyping, targeting the wzx and wzy genes, is able to detect distinct O-antigen forms, including E. coli , Shigella , Salmonella , Vibrio parahaemolyticus , Acinetobacter , Hafnia , and Proteus (Li et al, 2009, 2010; Guo et al, 2013; Hu et al, 2013; Chen et al, 2015; Duan et al, 2016; Yu et al, 2017). Our previous studies employed wzx and wzy for serotyping E. coli and Shigella by microarray (Li et al, 2006), wzx and wzy for serotyping Pseudomonas aeruginosa (Li et al, 2018) and wzm and wzt for serotyping 15 Legionella pneumophila serogroups by microarray (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Through genomic studies in recent years, numerous novel O-AGCs have been found in E. coli isolates (3,(6)(7)(8)(9)(10)(11). In Shiga toxin-producing E. coli (STEC) and enterotoxigenic E. coli (ETEC) studies, we found six (OgN1, OgN8, OgN9, OgN10, OgN12, and OgN31) and nine (OgN2, OgN3, OgN4, OgN5, OgN13, OgN14, OgN15, OgN16, and OgN17) novel O-AGCs, respectively, indicating that their wzx and wzy sequences were unique compared to those from known O-AGCs (less than 70% DNA sequence identity of closest pairs) (7,8).…”
mentioning
confidence: 99%
“…Generally, the O-AGC consists of three main classes of genes: (1) nucleotide sugar precursor synthesis genes, (2) glycosyltransferase genes, and (3) O-unit translocation and polymerization genes ( wzx / wzy in the Wzx/Wzy-dependent pathway and wzm / wzt in the ABC transporter pathway) [ 6 , 7 ]. In addition to the > 180 serogroups, many O genotypes of E. coli strains have been characterized according to their O-AGCs in recent years, very likely representing novel serogroups [ 8 , 9 , 10 ], however lacking the needed chemical structural data.…”
Section: Introductionmentioning
confidence: 99%